1996
DOI: 10.1104/pp.111.1.195
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Magnesium, Pyrophosphate, and Their Complexes as Substrates and Activators of the Vacuolar H+-Pumping Inorganic Pyrophosphatase (Studies Using Ligand Protection from Covalent Inhibitors)

Abstract: lnhibitors preferentially and covalently reactive with cysteine, arginine, histidine, and carboxyl-containing residues were inhibitory to the plant vacuolar H+-transporting inorganic pyrophosphatase (H+-PPase) from Vigna radiafa (mung bean) and Befa vulgaris (red beet), but hydrophobic compounds and those reactive with tyrosine and lysine were less effective. lnhibition by 1 -ethyl-3-(3-dimethylaminopropyl)carbodiimide, phenylglyoxal, and N-ethylmaleimide was decreased i n the presence of Mgz+ or mixtures of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…However, despite their kinetic equivalence, it is improbable that these results denote a direct interaction between Mg 2ϩ and the residues or domains that undergo covalent modification in all cases. Although the notion of direct protection is consistent with the finding that high affinity Mg 2ϩ protection of the VPPase not only applies to the carboxyl reagents, DCCD and EDAC, but also NEM, a sulfhydryl reagent, and phenylglyoxal, a reagent that preferentially reacts with guanidino side chains (31,32) and the fact that one cytosolic loop, that between transmembrane spans XIII and XIV, containing the Cys residue (Cys 634 ) responsible for substrate-protectable inhibition of the V-PPase by NEM (8,10), also contains Arg, Asp, and Glu residues, it does not reconcile two critical findings. It fails to explain why inhibition by DCCD is second order while EDAC, NEM, and phenylglyoxal inhibit the enzyme with first order kinetics (32) (11).…”
supporting
confidence: 67%
“…However, despite their kinetic equivalence, it is improbable that these results denote a direct interaction between Mg 2ϩ and the residues or domains that undergo covalent modification in all cases. Although the notion of direct protection is consistent with the finding that high affinity Mg 2ϩ protection of the VPPase not only applies to the carboxyl reagents, DCCD and EDAC, but also NEM, a sulfhydryl reagent, and phenylglyoxal, a reagent that preferentially reacts with guanidino side chains (31,32) and the fact that one cytosolic loop, that between transmembrane spans XIII and XIV, containing the Cys residue (Cys 634 ) responsible for substrate-protectable inhibition of the V-PPase by NEM (8,10), also contains Arg, Asp, and Glu residues, it does not reconcile two critical findings. It fails to explain why inhibition by DCCD is second order while EDAC, NEM, and phenylglyoxal inhibit the enzyme with first order kinetics (32) (11).…”
supporting
confidence: 67%
“…To further characterize the hydrolytic activity of Cl-PPase variants, we analyzed its dependence on the concentrations of the Mg 2 PP i complex, the true substrate of membrane PPase (20,21), at fixed concentrations of Na ϩ (10 mM) and K ϩ (100 mM). In addition to the effects on activity noted above, K m values decreased markedly (7.5-fold) in the S243A variant and less markedly (1.8-fold) in the K681N variant (Table 1).…”
Section: (A) and 8(b)mentioning
confidence: 99%
“…4B) (Fig. 2B) (6,7,30). Circular dichroism analysis revealed that K ϩ could elicit the secondary structure variations of H ϩ -PPase (31).…”
Section: Cysteine Pairs Ligand-free Kmentioning
confidence: 99%
“…This unique enzyme hydrolyzes PP i to generate H ϩ -motive force across vacuolar membrane in plants and plasmic membrane in prokaryotes (3,4). In addition, H ϩ -PPase requires Mg 2ϩ ion with PP i as the actual substrate (Mg 2 PP i ) for the hydrolyzing reaction (5,6). Furthermore, K ϩ is essential for stimulating type I H ϩ -PPase; however, Ca 2ϩ , Na ϩ , and F Ϫ inhibit its reaction (7).…”
mentioning
confidence: 99%